Aspects of Visual Stress in Visual Display Terminal Work - Mah, L J` (Canadian Journal of Optometry, 1983)
There have been frequent complaints arising from the operation of visual display terminals (VDT's). Radiation, ergonomics, and lighting factors have been intensely investigated, but visual stress has not received the same attention and study. This paper discusses inherent deficiencies in the images of a VDT, how the visual system reacts, and how fatigue results from the stress. Recommendations and solutions for the VDT operator are explored.